Hubungan keparahan karies gigi dengan konsumsi zat gizi dan status gizi anak sekolah dasar di Kecamatan Lhoknga Kabupaten Aceh Besar - Junaidi Junaidi; Madarina Julia; Julita Hendratini (Jurnal Gizi Klinik Indonesia, 2007)
Background: The prevalence of dental caries in children is high. Caries may prevent children from properly digest food, which is then impair nutritional intake and cause malnutrition.Objectives: To assess the relation between the severity of dental caries with nutritional status and nutrient intake of 8-10 years old school children, in the sub district of Lhoknga, Aceh Besar, Nanggroe Aceh Darussalam.Methods: This was a case-control study of 54 undernourished children as cases compared to 54 well-nourished children matched for age as control. The severity of dental caries was assessed by a dentist using a caries severity index used by the WHO.Results: The prevalence of dental caries in undernourished children was 90.7%, while in well-nourished children was 54.7%. The odds ratio (95% CI) for having dental caries in malnourished children was 7.3 (2.2-26.6), p<0,001. Compared to children without caries, the odds (95% CI) for undernourished in children suffering from severe dental caries was 10.3 (3.2-38.5). Dental caries was associated with lower intake of energy. The relative risk (95% CI) for children with severe caries to have inadequate energy intake was 4.9 (1.7–14.7), p<0.001.Conclusions: Nutritional status was associated with the severity of dental caries. Children with severe dental caries had lower energy intake.